2011
DOI: 10.1007/s11356-011-0453-0
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and distribution of metals by water lettuce (Pistia stratiotes L.)

Abstract: Further study on the bioavailability of metals in the water lettuce is needed for the beneficial use of metal-enriched plant biomass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 39 publications
(51 reference statements)
4
51
2
Order By: Relevance
“…Similar findings were also reported by Lu (2011) while working on lettuce that was a hyper accumulator of Fe, Pb and Cu.The same kind of findings were also reported by Mokhtar et al (2011) and Mishra and Tripath (2008).…”
Section: Total Increase In No Of Leaves -----------------------------supporting
confidence: 87%
“…Similar findings were also reported by Lu (2011) while working on lettuce that was a hyper accumulator of Fe, Pb and Cu.The same kind of findings were also reported by Mokhtar et al (2011) and Mishra and Tripath (2008).…”
Section: Total Increase In No Of Leaves -----------------------------supporting
confidence: 87%
“…Similar percentages of Zn removal were also observed when A. pinnata and L. minor were used (Vaseem and Banerjee, 2012). Other plant species such as T. latifolia (Sasmaz et al, 2008), C. ligulata, J. imbricatus (Miguel et al, 2013), E. acicularis (Ha et al, 2009), P. cummunis, T. angustifolia, C. esculentus (Chandra andYadav, 2011) and P. stratiotes (Lu et al, 2011) have shown potential to remediate Zn-contaminated waters.…”
Section: Phytoremediation Of Zn-contaminated Sitesmentioning
confidence: 53%
“…(Figure layout Barron-Cruz, 2011), P. cummunis, T. angustifolia, C. esculentus (Chandra and Yadav, 2011), A. caroliniana (Pandey, 2012), Alternanthera philoxeroides, Eichhornia crassipes and P. stratiotes (Agunbiade et al, 2009;Hua et al, 2012). Of those, the water lettuce (P. stratiotes) accumulates high levels of Mn in both roots and shoots (28290 and 26240 μg g −1 , respectively) and has been found to meet the characteristics of a good phytoremediator (Lu et al, 2011). Pokeweed (Phytolacca americana) was also able to accumulate high levels of Mn (approximately 20000 μg g −1 DW) (Dou et al, 2009).…”
Section: Phytoremediation Of Mn-contaminated Sitesmentioning
confidence: 98%
“…Biological approaches such as phytoremediation, i.e. the use of plants to clean up surface and groundwater contaminated by several pollutants, has received considerable attention because of its cost-effectiveness and environmentally friendly nature (Lu et al 2011). In this context, interesting perspectives for the utili-sation of forest plants in the reclamation of polluted waters have been evidenced (Guidi Nissim et al 2014.…”
Section: Introductionmentioning
confidence: 99%